The Effect of Core Stability Exercises on Dynamic Balance of Athletes with Chronic Ankle Sprain - Mohsen Sahranavard; Azar Aghayari; Alireza Motealleh; Akram Farhadi (Vesnu Publications, 2015)
Introduction: Functional ankle instability is the most common residual and debilitating symptoms of acute ankle sprain leading to lose of training and competition in athletes. The purpose of this randomized controlled trial was to investigate the effect of six weeks core stability training on dynamic postural control in individuals with chronic ankle sprain. Materials and Methods: Thirty people were randomized to the experimental or control group. A pretest-posttest control group design was used to evaluate the intervention. The 6-week intervention (core stability exercises) used for experimental group and conventional physiotherapy for both groups. All subjects were tested before the beginning of the core-stabilization training program (pretest) and immediately after the conclusion of the 6-week program (posttest). Pretesting and posttesting consisted of the star excursion balance test (SEBT) .Analysis of covariance compared outcomes between groups. The paired t test compared results within groups. A significant level of 0.05 was set for all analyses. Results: Results showed significant differences in mean of SEBT (in all directions) in the experimental and control group in post-test (P < 0.05), but improvement of balance in experimental group was greater than control group and this difference was significant (P < 0.05). Conclusion: It can be concluded that core stability training can lead to improve dynamic balance in patients with chronic ankle sprain. Therefore, this type of training is recommended to be considered as a therapeutic option for this population of patients.